A general theory of the complex pronotum morphology of treehoppers in Smiliinae and its relatives (Hemiptera: Membracidae) and its applicability to other subfamilies - Kanta SUGIURA; Tensho TERANO; Haruhiko ADACHI; Jin HAGIWARA; Keisuke MATSUDA; Kenji NISHIDA; Paul HANSON; Shigeru KONDO; Yasuhiko CHIKAMI; Hiroki GOTOH (European Journal of Entomology)
Treehoppers are characterized by exaggerated and three-dimensionally modified pronotal structures, known as "helmets". The treehopper pronotum has been studied mainly in terms of taxonomic diagnosis for over a century. It has recently been used as a model for studying the origin of evolutionary innovation and morphological diversification. However, the interspecific correspondence of traits, i.e., homology of pronotal parts, remains ambiguous due to (1) the extreme diversity in pronotal morphology and (2) little comparative study focused on homology. These problems hinder tracing the evolutionary history of treehopper pronotal morphology. Here, we investigate the homological relationships of pronotal structures among treehoppers, especially in the subfamily Smiliinae. We first investigate smiliine species, whose pronotal morphology is relatively simple, then expand to species with a more complex pronotum. Our comparative observations using six smiliine species reveal that four traits share the same positions and structures among these species: (1) the humeral angle, (2) the median carina, (3) the starting point of the median carina, and (4) the posterior apex of the pronotum, indicating that these traits are homologous across these species. Based on this homology hypothesis, we generalize the pronotal morphology and propose landmarks to help interpret the diversified pronotum of a clade including Smiliinae and its relatives. Finally, we confirm that this generalization can be applied to other treehopper subfamilies. Our homology-based approach can provide a strategy to recognize the trajectory of pronotal morphology, which is often difficult to trace.